2021
DOI: 10.1371/journal.pone.0252630
|View full text |Cite
|
Sign up to set email alerts
|

Plasma GDF-15 concentration is not elevated in open-angle glaucoma

Abstract: Aim Recently, the level of growth differentiation factor 15 (GDF-15) in blood, was proposed as biomarker to detect mitochondrial dysfunction. In the current study, we evaluate this biomarker in open-angle glaucoma (OAG), as there is increasing evidence that mitochondrial dysfunction plays a role in the pathophysiology of this disease. Methods Plasma GDF-15 concentrations were measured with ELISA in 200 OAG patients and 61 age-matched controls (cataract without glaucoma). The OAG patient group consisted of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…This may also be true in other diseases where mitochondrial involvement is suspected. This is in line with a recently published study, in which plasma levels of GDF-15 assessed in patients with open angle glaucoma were found to be strongly confounded by age and vascular diseases [ 41 ]. Due to the extremely diverse factors influencing serum concentrations of both FGF-21 and GDF-15, it is difficult to define an independent control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may also be true in other diseases where mitochondrial involvement is suspected. This is in line with a recently published study, in which plasma levels of GDF-15 assessed in patients with open angle glaucoma were found to be strongly confounded by age and vascular diseases [ 41 ]. Due to the extremely diverse factors influencing serum concentrations of both FGF-21 and GDF-15, it is difficult to define an independent control group.…”
Section: Discussionsupporting
confidence: 92%
“…GDF-15 is considered a stress-induced cytokine, and it may play a role in various pathophysiological processes, e.g., heart insufficiency, myocardial infarction, pulmonary hypertension, diabetes, metabolic syndrome, autoimmune diseases and cancer [ 37 , 38 ]. An association of higher GDF-15 levels and increasing age has also been described [ 39 , 40 , 41 ]. This is confirmed by our data.…”
Section: Discussionmentioning
confidence: 99%
“…The patient characteristics are presented in Tables 1 and 2 . A study [ 21 ] has confirmed that GDF15 levels are significantly affected by sex; therefore, in our study population, we conducted the statistical analyses separately between the male and female participants.…”
Section: Resultsmentioning
confidence: 99%
“…In the second step of analysis, we examined whether the first-year mean PA levels (continuous predictor) were associated with GDF-15 levels (continuous outcome measure) obtained at 1 year. These analyses were controlled for age, 15 sex, 29 body mass index (BMI), 30 MAPT group, inflammation assessed through C-reactive protein (CRP) and interleukin (IL)-6 blood levels measurement, 31 hypertension, 7 diabetes mellitus status, 7 hypercholesterolaemia, 7 cardiovascular disease (defined as having at least one of stroke, heart failure or ischaemic heart disease), 7 creatinine levels, 32 metformin medication, 14 cancer, 12 asthma or chronic obstructive pulmonary disease (COPD), 33 and mitochondrial function assessed through the measurement of circulating ATPase inhibitory factor 1 (IF1). 34 In the third step of analysis, the mediation analysis was performed using first-year mean PA level as predictor, 1-year GDF-15 levels as mediator and bodyweight changes calculated from 1-year to the subsequent time points (2 and 3 years in separate models) as the outcome.…”
Section: Statistical Analysesmentioning
confidence: 99%